2021
DOI: 10.3389/fped.2021.721857
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Interleukin-2 Receptor Level as a Marker of Hemophagocytic Lymphohistiocytosis in Children With Severe Dengue

Abstract: Dengue induced-hemophagocytic lymphohistiocytosis (HLH) is increasingly recognized as an important cause of secondary HLH. Early identification of dengue HLH and directed therapy for HLH may help to alter the outcomes in critically ill patients. Soluble interleukin-2 receptor (IL2R) is a useful inflammatory marker and is seen to correlate with HLH disease activity. There is scarcity of data on IL2R in pediatric dengue patients with HLH. All patients (age < 18 years) with severe dengue confirmed by posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…67,68 Very high levels of serum ferritin were observed in children with dengue-associated-HLH with mean serum ferritin of 34,593 ng/mL in comparison to the non-HLH group (Mean ferritin 3204 ng/mL). 69 Similarly, in another study from Puerto Rico, the median serum ferritin level (18,789 ng/mL) was very high in dengue-associated-HLH cases. 70 These studies have concluded that serum ferritin levels can be used to distinguish dengue -HLH from dengue fever.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…67,68 Very high levels of serum ferritin were observed in children with dengue-associated-HLH with mean serum ferritin of 34,593 ng/mL in comparison to the non-HLH group (Mean ferritin 3204 ng/mL). 69 Similarly, in another study from Puerto Rico, the median serum ferritin level (18,789 ng/mL) was very high in dengue-associated-HLH cases. 70 These studies have concluded that serum ferritin levels can be used to distinguish dengue -HLH from dengue fever.…”
Section: Discussionmentioning
confidence: 88%
“…Hyperferritinemia is reported to be associated with dengue‐associated‐HLH (HLH) 67,68 . Very high levels of serum ferritin were observed in children with dengue‐associated‐HLH with mean serum ferritin of 34,593 ng/mL in comparison to the non‐HLH group (Mean ferritin 3204 ng/mL) 69 . Similarly, in another study from Puerto Rico, the median serum ferritin level (18,789 ng/mL) was very high in dengue‐associated‐HLH cases 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of dengue-associated HLH in young children appeared to involve either steroids alone [ 48 , 70 , 71 ], immunoglobulin alone [ 72 ], or a combination of steroids and immunoglobulin [ 67 ]. Other agents like etoposide [ 73 ] were only occasionally used.…”
Section: Identification and Treatment Of Dengue-associated Hlh In You...mentioning
confidence: 99%
“…Bone marrow examination is not necessary when enough criteria have been fulfilled [ 32 ], although bone marrow aspiration seems to be safe in many reports involving adults and older children with dengue-associated HLH, consistent with the low 0.08% adverse event rate found in an audit performed by the British Society for Haematology across 63 hospitals [ 70 ]. Additionally, when it is available, specialized testing for elevated interleukin-2 receptor (i.e., CD25) can help distinguish dengue-associated HLH from severe dengue alone [ 71 ].…”
Section: Challenges In the Diagnosis And Treatment Of Dengue-associat...mentioning
confidence: 99%
“…Early recognition is imperative for a favorable outcome. Higher incidence of liver dysfunction and ARDS, increased requirement for invasive ventilation, and longer duration of ICU stay have been observed in dengue patients who develop HLH [ 26 ]. Soluble interleukin-2 receptor levels may act as a potential biomarker for dengue HLH [ 26 ].…”
Section: Management Of Complicationsmentioning
confidence: 99%